(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this paper, a second order sliding mode controller is applied for single-input single-output (SISO) electromechanical system. Regardless of the controller is enforced in turn overcomes the variations caused by the uncertainties due to an approximate model of the system utilized in the design procedure. An integral kind sliding surface is employed and therefore the stability and strength properties of the controller area unit evidenced by suggest that of Lyapunov stability theorem. The chattering phenomenon is considerably reduced adopting the switching gain with the best-known parameters of the system. Thus, the conferred controller is appropriate for long-term application to the systems those are having quick response closed-loop behaviors. The performance of the developed control scheme is valid by simulation in Math works Matlab and therefore the results are compared with the similar controllers conferred in the literature. All controllers applied to the electromechanical system to verify the performance in terms of time domain and performance error indices. The chattering drawback is sort of removed within the presented approach as compared with alternative controllers. This drawback is overcome employing a hyperbolic function within the switching control considering the small constant term just in case of the zero error to avoid the matter of zero division.